DAYA TERIMA DAN KADAR ZAT BESI NUGGET HATI AYAM DENGAN KOMBINASI TEMPE SEBAGAI PANGAN OLAHAN SUMBER ZAT BESI - Fauziah, Asti; Fajri, Roifah; Hermanto, Restu Amalia (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: The prevalence of anemia in Indonesia is still high, in girl adolescents 26.50%, childbearing women 26.9%, pregnant women 40.1% and infants 47%. Anemia can caused by inadequate dietary iron intake from foods. One of the effort that can be done is to improve food and nutrition by increasing consumption of foods containing iron. Chicken liver nugget with combination tempeh can consumed as processed food that increase iron intake as an effort to prevent anemia. Objective: This research aims to studying the acceptability and iron content of chicken liver nuggets with combination tempeh. Methods: The experimental design using Completely Randomized Design (CRD) with three repetitions of treatment, two repititions of analysis and five treatment levels with ratio between chicken liver and tempeh 10%: 90% (F1), 30%: 70% (F2), 50%: 50% (F3), 30%: 70% (F4) and 90% : 10% (F5). Data analysis was tested using Kruskal Wallis followed by Mann Whitney and One Way Anova. Iron levels were analyzed using a Atomic Absorption Spectrophotometry (AAS). Acceptance test of the product was done using a hedonic test. Results: There are differences in the acceptability of nuggets from various ratios of chicken liver and tempeh in color parameter (p = 0,000), odor (p = 0.017), texture (p = 0.049) and taste (p = 0,000). However, there are no differences in iron content from various ratios of chicken liver and tempeh (p = 0.877). Conclusion: There are differences in the acceptability of nuggets from various ratios of chicken liver and tempeh and there is no differences in iron nugget levels from various ratios of chicken liver and tempeh. Based on the results of the acceptability, the most preferred formulas were obtained including F3, F2 and F4.